ANALISIS PERAMALAN PERSEDIAAN STOK SEPEDA MOTOR BEKAS DENGAN PENERAPAN METODE SES STUDI KASUS SHOWROOM METRO MOTOR KISARAN - Windy Astika Mayang Sari; Bachtiar Efendi; Wan Mariatul Kifti (JUTSI: Jurnal Teknologi dan Sistem Informasi, 2022)
Abstract: Forecasting is an activity to predict future conditions by using past conditions testing. In forecasting there are many methods that can be used, the method used in this study is the Single Exponential Smoothing method. The Single Exponential Smoothing method is a moving average forecasting method where the data will be weighted that is sophisticated but still easy to use by an exponential function. The time parameter used in forecasting the stock inventory of used motorcycles is alpha 0.1 to 0.9, by finding the value error randomly until it finds the smallest alpha value. From the research that has been done, the results of the calculation of alpha (weight of the smoothing constant) used in forecasting the inventory of used motorcycles are: motorbike matic 0.2, motorbike 0.2, motorbike matic 0.6 because it has a very small error value Keywords : Forecasting; Showroom Metro Motor; stock. Abstrak: Peramalan (forecasting) merupakan suatu kegiatan untuk meramalkan keadaan dimasa yang akan datang dengan menggunakan pengujian keadaan dimasa lalu. Dalam peramalan terdapat banyak metode yang bisa digunakan, metode yang digunakan dalam penelitian ini adalah metode Single Exponential Smoothing. Metode Single Exponential Smoothing merupakan metode peramalan rata-rata bergerak dimana data akan diberi pembobotan yang canggih tetapi masih mudah untuk digunakan oleh sebuah fungsi exponential. Adapun parameter waktu yang digunakan dalam meramalkan persediaan stok sepeda motor bekas yaitu alpha 0.1 sampai 0.9, dengan mencari nilai error secara acak sampai menemukan nilai alpha yang terkecil. Dari penelitian yang telah dilakukan, didapatkan hasil perhitungan alpha (bobot konstanta penghalus) yang digunakan pada peramalan persediaan sepeda motor bekas yaitu : motor matic 0.2, motor bebek 0.2, motor matic 0.6 karena memiliki nilai error yang sangat kecil. Kata Kunci : Peramalan; Showroom Metro Motor; Persediaan.Kata Kunci : Peramalan, Showroom Metro Motor, Persediaan   ABSTRACT Forecasting is an activity to predict future conditions by using past conditions testing. In forecasting there are many methods that can be used, the method used in this study is the Single Exponential Smoothing method. The Single Exponential Smoothing method is a moving average forecasting method where the data will be weighted that is sophisticated but still easy to use by an exponential function. The time parameter used in forecasting the stock inventory of used motorcycles is alpha 0.1 to 0.9, by finding the value error randomly until it finds the smallest alpha value. From the research that has been done, the results of the calculation of alpha (weight of the smoothing constant) used in forecasting the inventory of used motorcycles are: motorbike matic 0.2, motorbike 0.2, motorbike matic 0.6 because it has a very small error value. Keywords : Forecasting, Showroom Metro Motor, stock